2001
DOI: 10.1109/77.919483
|View full text |Cite
|
Sign up to set email alerts
|

High-T/sub c/ SQUID gradiometer for mobile magnetic anomaly detection

Abstract: The prototype for a nitrogen-cooled high-T, SQUID gradiometer has been developed and is being evaluated for magnetic anomaly detection of underwater targets in mobile surveys. The prototype's design is based on the concept of the Three-Sensor Gradiometer (TSG). In the TSG approach, balance of two independent SQUID magnetometers is more difficult to attain than for conventional low-T, gradiometers in which signal subtraction occurs prior to a single SQUID stage. Experiments have been conducted using a platform-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…This dramatically reduces the dynamic range requirements on the outer SQUIDs by (largely) canceling the earth's field at the sensors. A mobile HTS SQUID gradiometer has been demonstrated that is based on this concept [4]. This system is nonetheless difficult to use as a basis for a tensor gradiometer because the localized feedback coils generate strong gradients that would affect the other gradiometers in the system.…”
Section: Agnetic Anomaly Detection (Mad) Applications Formentioning
confidence: 99%
“…This dramatically reduces the dynamic range requirements on the outer SQUIDs by (largely) canceling the earth's field at the sensors. A mobile HTS SQUID gradiometer has been demonstrated that is based on this concept [4]. This system is nonetheless difficult to use as a basis for a tensor gradiometer because the localized feedback coils generate strong gradients that would affect the other gradiometers in the system.…”
Section: Agnetic Anomaly Detection (Mad) Applications Formentioning
confidence: 99%
“…A number of tensor gradiometer systems, based on a wide range of different technologies including high temeprature SQUID devices, are under development (e.g., Clem et al 2001;Humphrey et al 2005;Leslie et al 2007;Wiegert et al 2007;Sunderland et al 2009;Keenan et al 2010). We anticipate that over the next decade full gradient tensor systems will be commercialized and be routinely used in next generation magnetic surveys for exploration.…”
Section: Resource Explorationmentioning
confidence: 99%
“…Magnetometers are widely used in many fields like navigation [1], geology [2], material science [3], magnetic anomaly detection [4], biomedicine [5][6][7], and basic scientific research. Different magnetometers have their own characteristics, which meet the requirements of different applications [8,9].…”
Section: Introductionmentioning
confidence: 99%